Atividade de enzimas oxidativas do Lentinula edodes em substratos agroindustriais - Regina, Magali (2009)
Basidyomycete Lentinula edodes has its related enzymatic activity mainly on the agribusiness waste kind used as a substrate. The objective of this work was to verify the activity of oxidative enzymes lacase (Lac), lignina peroxidase (LiP) and manganese peroxidase (MnP) of three L. edodes strains, in stationary system, cultivated the 25 degrees C, in the absence of light, in substrates wtih 20% of bran of rice, 1% of CaCO(3) and 79% of rice husk (CA), eucalyptus sawdust (SE), cassava bagasse (BM) and sugarcane bagasse (BC), adjusted to 60% of humidity. The Lac and MnP activities were bigger in eucalyptus sawdust (SE) and sugarcane bagasse (BC). The UP activity was not induced for tested substrates. The rice husk (CA) and cassava bagasse (BM) Substrates, although are not adequate to produce Lac or MnP, can be used as additives to increase the porosity, air availability and easy metabolism polysaccharides.